Alternatives for Decarbonising High-Temperature Heating Facilities in Residential Buildings - Juan Carlos Roca Reina; Johan Carlsson; Jonathan Volt; Agne Toleikyte (Energies)
The European Union aims to become carbon-neutral by 2050 and to reduce CO2 emissions by at least 55% by 2030 compared to 1990 levels. The buildings sector accounts for about 40% of its total energy consumption and is responsible for 36% of the total CO2 emissions. For this reason, decarbonising the heat consumed in buildings is key to meeting these targets. CO2 emission reduction in buildings typically involves upgrading heating facilities to enable heat supply at lower temperatures, or renovating buildings, both of which can be challenging for end users. This paper analyses reducing emissions from residential buildings using high-temperature or hybrid heat pumps that can produce water at the same temperature as condensing boilers. This enables a significant reduction in emissions from buildings for owners who cannot afford or do not want to undertake a full renovation or upgrade of their current hydronic facility. The methodology followed makes use of a simplified hourly energy model based on ISO 52016-1:2017. The results indicate that, depending on the EU region, reducing CO2 emissions in buildings through these types of systems is feasible, leading to CO2 emission reductions of 40% to 70%.